SADAR FINANSIAL: PELATIHAN MENGGUNAKAN INFORMASI DIGITAL DALAM MENGGALI TUJUAN MENABUNG PADA ANAK - Christian, Michael (Jurnal Pengabdian dan Kewirausahaan, 2018)
Almost all age groups have a difficult tendency in saving, especially in groups of children. Various ways that can be done in educating children in saving. Savings products for children from various Banks both public and private can be utilized in getting used to saving. Understanding the amount of savings that can be saved in a certain period of time should be known early on. It aims to prepare knowledge in children for discipline in saving and wise in the use of savings in the future. Through training in the form of the use of digital information in digging the goal of saving children is expected to be educated children about the discipline in saving, the amount of savings to be achieved and its use in realizing the wishes of children in the future. This research involves children from elementary school (SD) to high school (SMA) at the Orphanage. The results of this training explains that materials and implementations aimed at educating children in terms of savings that utilize digital information provide benefits and knowledge to participants. The ability factor of instructor/speaker is effective in giving the material to the participants. Device tools integrated with the Internet and the ability of participants to use digital information in terms of saving is still minimal and need to be familiarized.Keywords: Saving, Children, Digital Information, Training